The Relationship Between Learning Interest and Learning Outcomes in Food Processing and Presentation Subjects in Vocational High Schools - Rahwanda Syahgita Syauli; Elida Elida; Cici Andriani; Wiwik Indrayeni (Educia Journal, 2026)
Learning interest is widely recognized as an important psychological factor influencing students' academic achievement, particularly in vocational education where successful learning requires sustained engagement in both theoretical and practical activities. However, empirical evidence regarding its relationship with learning outcomes in culinary vocational education remains limited. This study aimed to examine the relationship between students' learning interest and learning outcomes in the Food Processing and Presentation subject among Grade XI Culinary students at SMK Negeri 1 Ampek Angkek. A quantitative correlational research design was employed involving all 44 Grade XI Culinary students using a total sampling technique. Primary data on learning interest were collected through a validated Likert-scale questionnaire, while secondary data on learning outcomes were obtained from students' official Summative Scope of Material assessment scores. Prior to the main study, the questionnaire was validated and demonstrated excellent reliability (Cronbach's Alpha = 0.952). The collected data were analyzed using descriptive statistics and Pearson Product-Moment correlation analysis after satisfying the assumptions of normality. The findings revealed that students generally demonstrated a high level of learning interest and achieved relatively good learning outcomes. Furthermore, the analysis identified a positive and statistically significant relationship between learning interest and learning outcomes (r = 0.425, p = 0.004), indicating that students with higher learning interest tended to achieve better academic performance. These findings suggest that learning interest serves as an important psychological resource that supports students' cognitive engagement and competency development in practice-oriented vocational learning. The study underscores the importance of implementing learner-centered pedagogical strategies that cultivate students' interest through authentic practical experiences, active participation, meaningful feedback, and collaborative learning. Strengthening students' learning interest should therefore be considered an integral component of efforts to improve learning quality and workforce readiness in vocational culinary education.